THE EFFECTIVENESS OF DELIVERING INFORMATION AND SOCIAL MESSAGES THROUGH RADIO PROGRAMS DURING THE COVID-19 PANDEMIC - Ronny Yudhi Septa Priana; Husnan Nurjuman (Management Department, Faculty of Economics and Business, Universitas Jambi, 2022)
This study explores the effectiveness of social messages conveyed by broadcasters in radio broadcast programs in changing the mindset of the listener community in dealing with the corona pandemic period (Covid 19). The object of research in this study is the capture power and changes in social attitudes of the people who live in the Serang Regency, especially those who listen to the radio. At the same time, the radio research subject is the Local Public Broadcasting Institute (LPPL) Serang Regency, which is located in Serang. The research data comes from the results of observations and interviews conducted by researchers on exposure to the message content conveyed by the announcer. The method used in this research is a survey to see how the community as listeners catches the message conveyed by the broadcaster as a message communicator and whether the listener community can accept the message. Research data in the form of findings in the field and the results of interviews complement the study's results. Through this research, researchers hope to get information about the program's effectiveness in delivering messages, especially during the current corona epidemic. The study's results are expected to be a reference, especially those that examine the effectiveness of broadcast programs on radio, the exposure of messages conveyed by broadcasters through radio broadcast programs, and recommendations for selecting the right media for delivering information.